A CROSS-SECTIONAL STUDY ON THE CLINICAL SIGNIFICANCE OF CREATININE, BLOOD UREA, AND CYSTATIN C IN PATIENTS WITH SYSTEMIC LUPUS ERYTHEMATOSUS AND LUPUS NEPHRITIS. - Bharti, Roli; Sinha, Anand (Student’s Journal of Health Research Africa, 2024)
Background The study aims to determine the clinical significance of renal biomarkers—specifically serum creatinine, cystatin C, and blood urea—in patients diagnosed with systemic lupus erythematosus (SLE), with a particular focus on evaluating their association with renal involvement and disease severity. Methods A total of 140 participants were enlisted, 70 of whom were SLE patients and 70 of whom were age- and sex-matched controls. Along with proteinuria levels, serum levels of creatinine, cystatin C, and blood urea were important variables that were assessed. Statistical analysis was also done to determine significance. Results Serum cystatin C levels were significantly elevated in SLE patients (mean 1.25 mg/L) compared to controls (mean 0.95 mg/L), p < 0.001. Similarly, serum creatinine (mean 1.02 mg/dL in SLE vs. 0.88 mg/dL in controls, p = 0.003) and blood urea levels (mean 35.6 mg/dL in SLE vs. 28.4 mg/dL in controls, p < 0.001) were higher in SLE patients. Proteinuria levels were markedly higher in SLE cases (mean 225 mg/day) compared to controls (mean 15 mg/day), p < 0.001. Serum cystatin C levels and proteinuria levels in SLE patients exhibited a favorable association, according to Pearson correlation analysis (r = 0.68, p < 0.001). Conclusion Serum creatinine, cystatin C, and blood urea are elevated in SLE patients with lupus nephritis, with cystatin C showing a strong association with proteinuria levels, indicating its potential as a sensitive biomarker for early renal impairment. These findings underscore the importance of incorporating cystatin C in routine assessments for better management of lupus nephritis. Recommendations Further, longitudinal studies are recommended to validate the predictive value of cystatin C and explore its role in guiding therapeutic interventions in lupus nephritis. The routine use of these indicators in clinical practice can help patients with SLE manage their renal involvement and detect it early.